Class A scavenger receptor MARCO negatively regulates Ace expression and aldosterone production - O'Brien, Conan JO; Ratti, Giorgio; Veida-Silva, Hellen; Haberman, Emma; Sweeney, Charles; Gordon, Siamon; Domingos, Ana I (eLife, 2025)
Aldosterone is a potent cholesterol-derived steroid hormone that plays a major role in controlling blood pressure via regulation of blood volume. The release of aldosterone is typically controlled by the renin–angiotensin–aldosterone system, situated in the adrenal glands, kidneys, and lungs. Here, we reveal that the class A scavenger receptor MARCO, expressed on alveolar macrophages, negatively regulates aldosterone production and suppresses angiotensin-converting enzyme (Ace) expression in the lungs of male mice. Collectively, our findings suggest alveolar macrophages as additional players in the renin–angiotensin–aldosterone system and introduce a novel example of interplay between the immune and endocrine systems.
Keywords: macrophages; endocrine; RAAS; aldosterone; adrenal; lung